Recombination in pe/ppe genes contributes to genetic variation in Mycobacterium tuberculosis lineages - Phelan, Jody E. (2018)
Background: Approximately 10 % of the Mycobacterium tuberculosis genome is made up of two families of genes that are poorly characterized due to their high GC content and highly repetitive nature. The PE and PPE families are typified by their highly conserved N-terminal domains that incorporate proline-glutamate (PE) and proline-proline-glutamate (PPE) signature motifs. They are hypothesised to be important virulence factors involved with host-pathogen interactions, but their high genetic variability and complexity of analysis means they are typically disregarded in genome studies. Results: To elucidate the structure of these genes, 518 genomes from a diverse international collection of clinical isolates were de novo assembled. A further 21 reference M. tuberculosis complex genomes and long read sequence data were used to validate the approach. SNP analysis revealed that variation in the majority of the 168 pe/ppe genes studied was consistent with lineage. Several recombination hotspots were identified, notably pe_pgrs3 and pe_pgrs17. Evidence of positive selection was revealed in 65 pe/ppe genes, including epitopes potentially binding to major histocompatibility complex molecules. Conclusions: This, the first comprehensive study of the pe and ppe genes, provides important insight into M. tuberculosis diversity and has significant implications for vaccine development.